Tony Allen : An Autobiography of the Master Drummer of Afrobeat - Allen, Tony, 1940-2020; Veal, Michael E., 1963- (Book collections on Project MUSE., 2013)
Tony Allen is the autobiography of legendary Nigerian drummer Tony Allen, the rhythmic engine of Fela Kuti's Afrobeat.